2002
DOI: 10.1002/jbm.a.10370
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenesis of human mesenchymal stem cells encapsulated in alginate beads

Abstract: Mesenchymal stem cells (MSCs) have the capacity for self-renewal and can form bone, fat, and cartilage. Alginate forms a viscous solution when dissolved in 0.9% saline and gels on contact with divalent cations. The viability and phenotype maintenance of chondrocytes in alginate beads have been well documented. However, little is known about the effect of microencapsulation in alginate on chondrogenesis of MSCs. In this study, human MSCs encapsulated in alginate beads were cultured in serum-free medium with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
141
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(158 citation statements)
references
References 42 publications
9
141
3
Order By: Relevance
“…Chondrocytes encapsulated in alginate remain differentiated, as opposed to cells cultured in monolayers, which become fibroblastic (Hauselmann et al, 1994). Moreover, MSCs in beads of this polymer that were cultured in medium containing TGF or BMP-2, -6, or -9 underwent chondrogenic differentiation (Ma et al, 2003;Majumdar et al, 2001). Bovine MSCs seeded in alginate beads also maintained a spherical form and increased the expression of chondrocyte-specific genes under TGF b1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocytes encapsulated in alginate remain differentiated, as opposed to cells cultured in monolayers, which become fibroblastic (Hauselmann et al, 1994). Moreover, MSCs in beads of this polymer that were cultured in medium containing TGF or BMP-2, -6, or -9 underwent chondrogenic differentiation (Ma et al, 2003;Majumdar et al, 2001). Bovine MSCs seeded in alginate beads also maintained a spherical form and increased the expression of chondrocyte-specific genes under TGF b1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Alginate is broadly used in in vitro experiments and provides an easy to control 3D cell culture environment. Previous studies have demonstrated differentiation of MSCs in alginate to NP-like cells [25,26] but direct comparison with medically approved, although for different applications, materials was not done before. Since a range of these medical devices are made of biological extracellular matrix molecules, we hypothesized that they may support equally to or better than alginate chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To induce MSC chondrogenesis growth factors such as transforming growth factor (TGF)-b1, 2 or 3 [18], bone morphogenetic protein-2 [19], -4 [20], -7 [21] or -14 (GDF-5) [22], have been described to facilitate MSCs differentiation, however the aim of this project was to focus on the differences caused by variety of matrixes. In particular, many studies already described culture of MSCs embedded in several types of scaffolds, such as agarose gels [23], alginate beads [24][25][26], synthetic polymers [27,28] and other biomaterials [29][30][31][32]. These studies provide clear evidence that there is a need of a cell support for enhancing cell-cell and cell-matrix interactions and creating a 3D environment.…”
Section: Introductionmentioning
confidence: 99%
“…The immobilization of cells in particles is widely discussed in tissue engineering; the possibility to encapsulate non-human cells reduces the host's immune system response, facilitating transplantation as an alternative to the limited donor tissues available [1]. The technique of cell encapsulation is being used for the production of "Bio artificial Pancreas" [2], immunobarrier for islet cells transplantation [2][3][4], and the encapsulation of stem cells [5,6]. Encapsulation of living cells was also suggested for the production of chemicals such as alcohol, organic acids, steroids, antibiotics, vaccines [7].…”
Section: Introductionmentioning
confidence: 99%